Respon Masyarakat Terhadap Implementasi Sertifikasi Forest Stewardship Council (FSC) di Hutan Bambu (Studi Kasus Kecamatan Golewa Barat, Kabupaten Ngada, Provinsi Nusa Tenggara Timur) - Juniawan Amir; Mamie Elsyana Pellondo'u; Nixon Rammang (Wana Lestari, 2024)
FSC certification ensures sustainable forest management and has an impact on the economic, ecological, social and cultural aspects of communities around bamboo forests. FSC certification ensures that certification group members comply with forest management in accordance with certification and comply with land legality so as to provide quality and sustainable forest products. FSC certification makes it easier for certification group members to provide international sales markets because FSC has been recognized internationally. The level of readiness of knowledge, attitudes and behavior regarding the implementation of FSC certification is currently still very limited, as is its application in bamboo forests. The response of the community as members of the FSC certification group is not yet known, making this research important to carry out. This research aims to measure the knowledge, attitudes and behavior of FSC certification group members regarding the implementation of FSC Certification in the bamboo forest of West Golewa District, Ngada Regency, East Nusa Tenggara Province in July 2023. This research was conducted using a qualitative descriptive method and distributed questionnaires to 64 respondents. is a member of the FSC certification group. Data collection techniques were carried out using field observation techniques and informal discussions, interviews and questionnaires. The research results show that the level of knowledge of certification group members regarding the implementation of FSC certification is in the sufficient category (60.9%), the attitude of FSC certification group members towards the implementation of FSC Certification is in the Sufficient category (53%), and the behavior of FSC certification group members towards the implementation of FSC certification in the sufficient category (58%). The community's response to the implementation of FSC certification is in the positive response category but there needs to be increased education and assistance for the community as members of the certification group.